2008
DOI: 10.1073/pnas.0711863105
|View full text |Cite
|
Sign up to set email alerts
|

BDNF is essential to promote persistence of long-term memory storage

Abstract: Persistence is a characteristic attribute of long-term memories (LTMs). However, little is known about the molecular mechanisms that mediate this process. We recently showed that persistence of LTM requires a late protein synthesis-and BDNF-dependent phase in the hippocampus. Here, we show that intrahippocampal delivery of BDNF reverses the deficit in memory persistence caused by inhibition of hippocampal protein synthesis. Importantly, we demonstrate that BDNF induces memory persistence by itself, transformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
422
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 595 publications
(443 citation statements)
references
References 36 publications
(58 reference statements)
15
422
1
5
Order By: Relevance
“…The results are compatible with a role of the recently described hippocampal mechanism of memory persistence for one-trial avoidance and contextual fear conditioning in rats (12,13). Methylphenidate stimulates dopamine release in the forebrain by influences on the dopamine vesicular transporter (24)(25)(26)(27), and it was reported long ago to enhance learned behaviors in rats (28,29) and, more recently, in humans (30).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The results are compatible with a role of the recently described hippocampal mechanism of memory persistence for one-trial avoidance and contextual fear conditioning in rats (12,13). Methylphenidate stimulates dopamine release in the forebrain by influences on the dopamine vesicular transporter (24)(25)(26)(27), and it was reported long ago to enhance learned behaviors in rats (28,29) and, more recently, in humans (30).…”
Section: Discussionsupporting
confidence: 73%
“…Their persistence depends on several factors: the degree of emotional arousal at the time of consolidation (3, 7), age (8-11 years), perhaps circadian oscillations (6), and other factors (5). A specific BDNF-dependent mechanism for memory persistence has been described in the hippocampus of rats, which is activated around 12 hours after training (12,13).…”
mentioning
confidence: 99%
“…This effect was partly reversed by cross-fostering and fully reversed by the administration of DNMT inhibitors in adulthood (Roth et al, 2009). Given the established role for BDNF in fear learning and cognitive function in general (Alonso et al, 2005;Bekinschtein et al, 2008a;Bekinschtein et al, 2008b;Lubin et al, 2008), these results indicate that early-life experiences may increase the susceptibility to PTSD at least in part through epigenetic regulation of the BDNF gene, but additional studies are required to test this hypothesis directly. Overall, these findings, as well as those from Michael Meaney's lab, are consistent with the emerging unifying hypothesis that the accumulation of aberrant epigenetic marks over the lifespan may be a driver of PTSD-related cellular, cognitive, and physiologic changes.…”
Section: Role Of Bdnf In Ptsdmentioning
confidence: 88%
“…A recent series of studies found that the brain-derived neurotrophic factor BDNF gene locus, which is associated with learning and memory in general and with fear memory in particular (Alonso et al, 2005;Bekinschtein et al, 2007;Bekinschtein et al, 2008a;Bekinschtein et al, 2008b), is also subject to memory-associated changes in DNA methylation. Specifically, contextual fear conditioning was associated with decreased methylation and increased expression of BDNF exon IV, and this effect was regulated by the NMDA receptor Figure 3).…”
Section: Epigenetic Mechanisms In Hippocampus-dependent Fear Consolidmentioning
confidence: 99%
“…Furthermore, the specific mechanisms by which exercise increases BDNF expression in the brain and by which these increases translate into improvements in memory remain unclear. The role of BDNF in learning and memory has been well established [8][9][10][11]: BDNF has a wide range of short-term and long-term effects on neurons, most of which are thought to be mediated by its binding to the tyrosine kinase B (TrkB) Receptor, and the consequent activation of plasticity-related signalling cascades [12]. One such signalling cascade is the ERK (extracellular signal-related kinase) pathway [13], which has been shown to be essential to a number of forms of learning and memory [14,15].…”
Section: Introductionmentioning
confidence: 99%